Libraries post Covid 19 pandemic: Considerations from Mexico - Jaramillo, María Guadalupe Venteño; Valencia, Jorge (Access: An International Journal of Nepal Library Association, 2022)
The objective of this paper is to show a general description of the first actions that librarians carried out in Mexico in the face of the Covid 19 pandemic, both to respond to the user in their demands for information, and to carry out their professional and leisure activities. The actions undertaken by librarians of academic libraries in the context of the pandemic are presented. Libraries in Mexico are one of the main sources of access to documentary information. In general, all types of libraries had to suspend their services during the pandemic and initiate protocols to restart functions. In this paper we have specifically addressed the contingency measures implemented in university libraries. Academic libraries had to adapt quickly to continue offering documentary and information services and with this, continue to carry out their functions in the development of professional training activities, technological developments, research, administration, and extension of culture. Both university libraries and users (students, professors, researchers, and administrative staff) had to adapt to the contingency since in most cases protocols were established both for prevention to avoid contagion and for user care. This document is the result of the research carried out based on the information answered by 40 libraries studied, to whom an instrument was applied. The literature on current topics was consulted in various databases and information from the websites of the libraries themselves. Information was also collected from approximately 20 academic events organized by library associations and other information professionals, such as the AMBAC (Civil Association of Librarians), the Library College of Mexico and the IFLA (International Federation of Library Associations and Institutions).